Global health competencies in UK postgraduate medical training: a scoping review and curricular content analysis. Issue 8 (23rd August 2019) - Al-Shakarchi, Nader; Obolensky, Lucy; Walpole, Sarah; Hemingway, Harry; Banerjee, Amitava
Abstract : Objective: To assess global health (GH) training in all postgraduate medical education in the UK. Design: Mixed methodology: scoping review and curricular content analysis using two GH competency frameworks. Setting and participants: A scoping review (until December 2017) was used to develop a framework of GH competencies for doctors. National postgraduate medical training curricula were analysed against this and a prior framework for GH competencies. The number of core competencies addressed and/or appearing in each programme was recorded. Outcomes: The scoping review identified eight relevant publications. A 16-competency framework was developed and, with a prior 5-competency framework, used to analyse each of 71 postgraduate medical curricula. Curricula were examined by a team of researchers and relevant learning outcomes were coded as one of the 5 or 16 core competencies. The number of core competencies in each programme was recorded. Results: Using the 5-competency and 16-competency frameworks, 23 and 20, respectively, out of 71 programmes contained no global health competencies, most notably the Foundation Programme (equivalent to internship), a compulsory programme for UK medical graduates. Of a possible 16 competencies, the mean number across all 71 programmes was 1.73 (95% CI 1.42 to 2.04) and the highest number were in paediatrics and infectious diseases, each with five competencies. Of the 16 core competencies, global burden of disease and socioeconomic determinants of health were the two most cited with 47 and 35 citations, respectively. 8/16 competencies were not cited in any curriculum. Conclusions: Equity of care and the challenges of practising in an increasingly globalised world necessitate GH competencies for all doctors. Across the whole of postgraduate training, the majority of UK doctors are receiving minimal or no training in GH. Our GH competency framework can be used to map and plan integration across postgraduate programmes.